The association of gut microbiota, immunocyte dynamics, and protein–protein ratios with tuberculosis susceptibility: a Mendelian randomization analysis - Hanxin Wu; Weijie Ma; Liangyu Zhu; Li Peng; Xun Huang; Lei Zhong; Rui Yang; Bingxue Li; Weijiang Ma; Li Gao; Xinya Wu; Jieqin Song; et al. (Scientific Reports)
Abstract This study focused on the relationships among gut microbiota, plasma protein ratios, and tuberculosis. Given the unclear causal relationship between gut microbiota and tuberculosis and the scarcity of research on relevant plasma protein ratios in tuberculosis, Mendelian randomization analysis (MR) was employed for in-depth exploration. By analyzing the GWAS data of individuals with European ancestry (the FinnGen dataset included 409,568 controls and 2613 cases), using the two-sample MR method, we focused on evaluating the impact of immunocyte-mediated gut microbiota on tuberculosis and the associations between 2821 plasma protein-to-protein ratios and tuberculosis. Particularly, the mediation effect was emphasized in the exploration. The results showed that 19 gut microbiotas were associated with tuberculosis. An7 indirectly affected tuberculosis through immunocyte (CD4 on CM CD4+), with a masking effect ratio of 0.008, demonstrating immune cells’ mediating role in the association between gut microbiota and tuberculosis. Meanwhile, the MR analysis revealed that 127 plasma protein-to-protein ratios were associated with tuberculosis. In conclusion, this study not only confirmed the impact of immunocyte-mediated gut microbiota on tuberculosis and clarified the mediating mechanism therein but also identified plasma protein-to-protein ratios related to tuberculosis, providing novel and valuable ideas for diagnosing and treating tuberculosis.